Synergistic and antagonistic interactions between bednets and vaccines in the control of malaria - Artzy-Randrup, Yael (Proc Natl Acad Sci U S A, 2015)
It is extremely likely that the malaria vaccines currently in development will be used in conjunction with treated bednets and other forms of malaria control. The interaction of different intervention methods is at present poorly understood in a disease such as malaria where immunity is more complex than for other pathogens that have been successfully controlled by vaccination. Here we develop a general mathematical model of malaria transmission to examine the interaction between vaccination and bednets. Counterintuitively, we find that the frailty of malaria immunity will potentially cause both synergistic and antagonistic interactions between vaccination and the use of bednets. We explore the conditions that create these tensions, and outline strategies that minimize their detrimental impact. Our analysis specifically considers the three leading vaccine classes currently in development: preerythrocytic (PEV), blood stage (BSV), and transmission blocking (TBV). We find that the combination of BSV with treated bednets can lead to increased morbidity with no added value in terms of elimination; the interaction is clearly antagonistic. In contrast, there is strong synergy between PEV and treated bednets that may facilitate elimination, although transient stages are likely to increase morbidity. The combination of TBV with treated bednets is synergistic, lowering both morbidity and elimination thresholds. Our results suggest that vaccines will not provide a straightforward solution to malaria control, and that future programs need to consider the synergistic and antagonistic interactions between vaccines and treated bednets.